Analysis of the Quality of the Role of Gold Savings Products at PT. Pegadaian (PERSERO) Madina Sharia Service Unit - Nabilah Salsabilah; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Pegadaian Syariah is a state-owned company engaged in the field of non-bank financial institutions in the form of a unit from PT. Indonesian Pawnshop. Pegadaian Syariah is generally in charge of distributing financing in the form of providing loan money to people in need based on the pawn law. In addition, sharia pawnshops also have various products including Gold Savings. The Gold Savings product provides a new account opening service in the form of gold savings with a very cheap minimum deposit. The purpose of this study is that the author knows how the company in managing the role of the quality of gold savings products at PT. Pegadaian (prsero) UPS Madina. In this study the authors used a qualitative descriptive method with data collection techniques using literature studies and interviews with several customers at PT. Pegadaian (Persero) UPS Madina. The results of this study state that gold savings products play a very important role in helping people invest in gold using the saving method. In addition to a low minimum deposit, an easy service system, also the system used at PT. Pegadaian (Persero) UPS Madina applies sharia-compliant principles so that customers are also avoid the practice of usury.